EFFECTS OF DEXMEDETOMIDINE ON HAEMODYNAMICS IN PATIENTS UNDERGOING INTRA-ABDOMINAL LAPAROSCOPIC SURGERIES: A COMPARATIVE STUDY - VISHWANATH,; BALARAJU.T.C,; SWATHI RAJASHEKAR,; SREEKANTHA, (International Journal of Pharma and Bio Sciences, 2015)
Laparoscopic surgeries are advantageous over conventional laparotomy. Pneumoperitoneum and intraoperative positional changes cause significant haemodynamic changes for which various drugs have been used to attenuate these changes. We performed a prospective, randomised, double blind study to evaluate the effect of dexmedetomidine. Sixty American society of anaesthesiologist’s physical status I and II patients undergoing intra-abdominal laparoscopic surgeries, were randomly allocated to receive either dexmedetomidine 1mcg/kg intravenously over 10minutes before induction of anaesthesia and 0.4mcg/kg/hrintraoperatively till the end of pneumoperitoneum (group D, n=30) or 0.9% saline at the same rate as dexmedetomidine (group S, n=30). Intraoperative heart rate and mean arterial pressures were monitored continuously and charted after bolus drug administration, 1min after induction, 1min after intubation, and after pneumoperitoneum at 15min interval till end of pneumoperitoneum and postoperative period. Time of response to verbal commands, tracheal extubation and time to become fully awake is noted. Patients were observed for any adverse events like bradycardia, tachycardia, hypotension, hypertension and postoperative nausea and vomiting. Heart rate and mean arterial pressure variation in dexmedetomidine group were less after pneumoperitoneum when compared to control group with p value <0.001 which is statistically significant. No significant differences in the parameters of recovery were observed between both the groups. Dexmedetomidine provides intra and postoperative haemodynamic stability during the laparoscopic surgery without affecting the recovery. It causes bradycardia and hypotension which is clinically insignificant.